Computational aerodynamics analysis of a bluff body with rotating cylinder as drag reducer - Kamid, Muhammad Irfan; Mohammad Ali, Hidayatullah; Mohd. Rafie, Azmin Shakrine (Aerospace Society Malaysia, 2023)
This study is aimed to address the issue of dangerous emissions into the environment by the operation of large container lorries. These big vehicles use much of their engine power to overcome the aerodynamic drag due to their movement, which also means a lot of fuel is being burned in this process. To reduce the fuel consumption, hence the gas emissions, the aerodynamic efficiency of the vehicle can be improved through its design. Based on this notion, the main objective of this work is to analyse the impacts from the use of a rotating cylinder as a drag reducer for heavy-duty vehicles. The incorporation of the rotating cylinder is expected to be able to reduce the drag forces acting on the vehicles and also increase their design aerodynamic efficiency. For this study, a container lorry is modelled and analysed using the computational simulation software, ANSYS with several different placements of the rotating cylinder around the lorry as its drag reducers. The obtained results indicate that the use of the cylinder can reduce drag by as much as 36 in comparison to the baseline design of the container lorry without rotating cylinder. It is observed that the cylinder helps to lessen the airflow circulating at the back and top of the container lorry, subsequently lower its drag coefficient. All in all, the findings from this study demonstrate the potential of using rotating cylinders as drag reducers to solve the issue of gas emissions from container lorries.